Dietary synbiotic improves the growth performance, survival and innate immune response of Gibel carp (Carassius auratus gibelio) juveniles - Fahimeh Mahghani; Ahmad Gharaei; Mostafa Ghaffari; Raza Akrami (International Journal of Aquatic Biology, 2014)
This study was conducted to evaluate the effect of dietary synbiotic (Biomon imbo) on the growth performance, survival and innate immune response of Gibel carp (Carassius auratus gibelio) juveniles. Fish with initially average weight 15.5±0.2 g were randomly distributed into tanks (20 fish/tank). Basal diets (Biomar) were supplemented with 0 (control), 0.5, 1.0, 1.5 and 2.0 g symbiotic per kg-1 in a totally randomized design trial in triplicate group. At the end of the experiment (60 days), innate immune parameters (serum Ig levels and lysozyme activity) and growth factors (ﬁnal weight, weight gain (WG %), speciﬁc growth rate (SGR) and food conversion ratio (FCR)) were assessed. According to our results, the growth performance and feed efficiency improve in fish fed on the diet containing 2.0 g kg-1 synbiotic (P<0.05). There were no significant differences in survival among all treatments (P>0.05). Lysozym activity and serum Ig levels in fish fed the 2.0 g kg-1 synbiotic diet was higher compared to other experimental groups (P<0.05). These results indicate that synbiotic can be considered as a beneﬁcial dietary supplement for improving the immune response and growth performance Gibel carp (Carassius auratus gibelio) juveniles.